Comparative Assessment of Nutritional Composition in Selected Freshwater Fishes from Amravati City - Dr. Siddhu. H. Rathod (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study assesses the nutritional composition of nine freshwater fish species Rasbora daniconius, Wallago attu, Pangasius pangasius, Channa punctatus, Notopterus notopterus, Labeo rohita, Anguilla bengalensis, Barilius tileo, and Ompok pabda—collected from the Amravati fish market. Moisture and ash contents, key indicators of nutritional value, were analyzed. Moisture levels ranged from 52.52 ± 0.69% in Pangasius pangasius to 76.16 ± 0.09% in Channa punctatus, while ash content varied from 0.76 ± 0.24% in Barilius tileo to 1.58 ± 0.01% in Channa punctatus (P < 0.05). Despite their relatively smaller size compared to marine species, these fishes offer significant protein, moisture, and mineral content, making them a vital, low-cost nutritional source for populations in the Amravati region. Their nutritional richness suggests strong potential for promoting dietary diversity, improving food security, and supporting local fisheries through sustainable utilization.
Keywords: Freshwater fishes; Total Protein; Ash; Moisture